Oral health among Dutch elite athletes prior to Rio 2016 - Kragt, L.; Moen, M. H.; Van Den Hoogenband, C.-R.; Wolvius, E. B. (The Physician and Sportsmedicine, 2019)
Objectives: Elite athletes are at high risk for poor oral health. A screening program to assess oral health and create dental awareness can improve oral health among elite athletes but has not been performed in the Netherlands before. We summarize the first results from such a screening conducted in Dutch elite athletes of the Nederlands Olympisch Committee*Nederlandse Sport Federatie (NOC*NSF, Dutch Olympic Committee).